Prolonged Analgesic Efficacy of Articaine with the Addition of Tramadol in Axillary Brachial Plexus Block - Kilinc, Leyla (Sisli Etfal Hastan Tip Bul, 2019)
OBJECTIVES: Articaine is a rapid-onset, short-duration, local anesthetic. The aim of this study was to study the effect of adding tramadol to articaine in an axillary block to prolong the analgesic effect. METHODS: This study was conducted with 60 patients of American Association of Anesthesiologists classification I or II and aged 18 to 60 years who underwent hand or forearm surgery with an axillary plexus block using a nerve stimulation technique. The patients were randomized into 2 groups: Group A (n=30) received 40 mL 1% articaine and Group AT (n=30) was administered 40 mL 1% articaine with 100 mg tramadol. The onset of sensory block, motor block, duration of sensorial block and motor block, duration of analgesia and hemodynamic parameters were recorded before the block and 5, 10, 20, 30, 60, 120, 180 minutes after the local anesthetic injection. RESULTS: The sensory block duration in Group AT (187.5±13.0 min) was significantly longer than that of group A (140.78±8.74 min) (p<0.02). The motor block duration in Group AT (137.4±3 min) was significantly longer than that seen in Group A (93.71±9.6 min) (p<0.01). The duration of analgesia was longer in Group AT (218.8±18.2 min) than in Group A (170.8±17.2 min) (p<0.05). In group AT, 2 patients experienced the side effect of nausea and 1 patient had hypotension in the postoperative period. CONCLUSION: This study demonstrated that the addition of 100 mg of tramadol to articaine used for an axillary plexus block prolonged analgesia.